2011
DOI: 10.1039/c1dt10752f
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the isomerization and photophysical properties of a novel 2,2′:6′,2′′-terpyridine-based ligand and its complexes

Abstract: A novel 2,2':6',2''-terpyridine-based ligand L and its complexes [ML(2)](ClO(4))(2)·CH(2)Cl(2) (M = Cd 1, Zn 2, Cu 4, Mn 5), [CoL(2)](ClO(4))(2)3, CdLI(2)6 and CdL(SCN)(2)7 were synthesized and fully characterized. The crystal structures of 1-6 were solved by single crystal X-ray diffraction analysis. The linear absorption and emission properties, and third-order nonlinear optical (NLO) properties of all the complexes were systematically investigated. The equilibrium of the trans- and cis- isomers of L was stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…It has been reported that these metallopolyynes are white powders and they possess high transparency towards visible light, which properties, plus their good solution processability, make them good candidates for OPL materials. Although Ru 2+ and Zn 2+ complexes with terpyridines have been reported with good NLO properties and large TPA cross section, which could be used for their application as OPL materials, their strong absorption in the visible region currently limits their use as optical limiters, though it may be possible to obtain polymers with suitable properties by choosing the right ligands.…”
Section: Nonlinear Optical Properties Of Terpyridine Ligands and Theimentioning
confidence: 99%
“…It has been reported that these metallopolyynes are white powders and they possess high transparency towards visible light, which properties, plus their good solution processability, make them good candidates for OPL materials. Although Ru 2+ and Zn 2+ complexes with terpyridines have been reported with good NLO properties and large TPA cross section, which could be used for their application as OPL materials, their strong absorption in the visible region currently limits their use as optical limiters, though it may be possible to obtain polymers with suitable properties by choosing the right ligands.…”
Section: Nonlinear Optical Properties Of Terpyridine Ligands and Theimentioning
confidence: 99%
“…Two-photon absorption dyes 2995 dye 3 formed a 2-D framework through π-π stacking interactions (green dashed line, the shortest distance is 3.475 Å, plum dashed line, the shortest distance is 3.035 Å) between the neighboring dimers along the c-axis. In addition, C-HÁ Á ÁI interactions (d (H33Á Á ÁI2) [15], which is assigned to π-π ⁄ transitions [16]. The absorption profile and maxima of all of the compounds are almost identical in different solvents, suggesting that ground state electronic structures are independent of solvent polarity and small dipole moments associated with the ICT transitions.…”
Section: Preparation Of Ligand and Dyes 1-5mentioning
confidence: 97%
“…This is accounted for the terpyridine unit mobility, which can adopt different conformations, breaking the chain conjugation. According to the literature [35] three different conformations can be assigned to this group: cis-cis, trans-trans and cis-trans which in turn would result in changes of the energy levels in the excited state, depending on the chemical environment.…”
Section: Photoluminescence Studiesmentioning
confidence: 99%